PENGARUH TINGKAT BAGI HASIL TERHADAP MINAT MENABUNG DI BANK SYARIAH - WIRDAYANI WAHAB (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2016)
The research theme is the concept of the bank in accordance with Islamic economics. The research was conducted on the sharia banking industry in Indonesia. The objective of the research is to see the effect of the level profit and profit sharing against consumer interest. The variables studied were: 1) Profit and lost sharing as an independent variable, 2) Consumer interest as the dependent variable. The study is quantitative. This type of research is causality. The analytical tool used is multiple linear regressions. The data used is secondary data obtained from Bank Indonesia. The data in use are: 1) A savings account administrative Bank Umum Syariah and Usaha Unit Syariah, 2) A savings account administrative Financing Bank Pembiayaan Rakyat Syariah, 3) The number of accounts in sharia banks. The results of this study are: profit and loss sharing significantly affects consumer interest.